Estudo comparativo de diferentes fixações na técnica de mandibulalotomia - Araujo, Thiago Caixeta (2008)
The number of tumors in the oral cavity is increasing significantly, mainly, due to the use of tobacco. In general, resection is the treatment for these tumors. This process is made through the access to the oral cavity using the mandibulotomy technique. For that, different cuts can be made in the mandible, in function of tumor position and patient condition. The cuts fixation, in general, are made using miniplates and titanium screws or steel wires. In this aspect, many clinical doubts exist, under the biomechanics perspective, on which is the best surgical procedure would be. This work aims to evaluate two types of cuts in a mandible, midline and paramidline, using different fixation sets with miniplates. Simplified finite element models were used to verify which was the best configuration through analysis of the stability level and stress gradient. At the same time, a human jaw photoelastic model was used, where two types of cuts were analyzed: midline and paramidline, with two types of knotting for wires, parallel and opposite. The critical stress levels were evaluated for different cross sections. Additionally, a visual inspection of relative displacement was made between the cross sectional. It was observed that the number of bolts does not influence the stability when the same number of miniplates is used. Using only one miniplate, the medium cut presents better stability than the paramidline cut. Using two miniplates in the setting, despite the small difference, the paramidline presents better stability, while the best configuration is that with two miniplates and six screws. A significant increase in the obtained stress level was observed with two miniplates and six screws fastened.